Prevalence of Cytomegalovirus infection among pregnant women with cord blood examination - Fareed Yalda, Karam; Abdalla Goreal, Amer (Journal of Contemporary Medical Sciences, 2023)
Objective: This study aimed at determining the prevalence of CMV infection among pregnant women at the end of pregnancy and CMV transmission to their newborns. Methods: This is cross sectional study, 213 pregnant women at delivery and their newborn babies from the Obstetrics and Gynecology Hospital in Duhok /Iraq were enrolled. A questionnaire was prepared to be answered by participants, including age, place of residence, educational level, and obstetric history as number of births, any bad obstetric history such as abortion, still birth, intrauterine growth retardation, congenital anomalies after birth.3-5 ml of blood was drawn from each woman and examined by ELISA kit to check for the presence of Anti CMV IgM, IgG, then IgG avidity test for those with positive (IgG and IgM). Samples of cord blood were collected from newborns after birth and checked for the presence of CMV IgM by ELISA and CMV –DNA by conventional PCR using specific primers to diagnose congenital infection and determine the rate of viral transmission from infected women. Results: Serological examinations showed that 212 (99.5%) participants were CMV-IgG positive, 15 (7%) were positive for anti-CMV IgM and IgG antibodies, IgG avidity test for 15 women were of high avidity (>89%) which indicated non primary infections. Cord blood of newborns of those 15 women with positive IgG and IgM tested negative for Anti CMV IgM by ELISA and no CMV-DNA was detected by PCR, which revealed no transmission from those pregnant to their newborns. Conclusion: This study demonstrated high prevalence of CMV among examined pregnant women in Duhok city which makes them prone to non-primary infection. IgG avidity test is of high efficacy to interpret the detection of IgG and IgM together in pregnant women. Cord blood examination for the existence of CMV-IgM and CMV-DNA after delivery could exclude congenital infection.